2020
DOI: 10.1177/1558925020940104
|View full text |Cite
|
Sign up to set email alerts
|

Triclosan applications for biocidal functionalization of polyester and cotton surfaces

Abstract: For 20 years, antibacterial functionalization has been one of the most attractive research fields in the textile industry. Nowadays, globalization has spread the microorganisms everywhere and produced many epidemics and pandemics such as smallpox, cholera, tuberculosis, yellow fever, Spanish flu, and coronavirus. The textile materials treated with triclosan would be a strong alternative to obtain antibacterial function against microorganisms for the medical applications, such as face masks, lab coats, and woun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Triclosan is a chemical included in many common household products like soap, toothpaste, and hand soap that is used to reduce or prevent bacterial infection. Multiple studies have found that using products with triclosan could contribute to the spread of bacteria that are resistant to antibiotics and other types of biocides (Orhan, 2020). This concern stems from research showing that exposure to triclosan can lead to bacterial target mutations that confer isoniazid resistance and designates for mutants with sensitivity to multiple antimicrobial medicines via the formation of multidrug-resistant efflux pumps, as described in Freundlich et al (2009).…”
Section: Antibiotic Susceptibility Testing and Mar Index Evaluationmentioning
confidence: 99%
“…Triclosan is a chemical included in many common household products like soap, toothpaste, and hand soap that is used to reduce or prevent bacterial infection. Multiple studies have found that using products with triclosan could contribute to the spread of bacteria that are resistant to antibiotics and other types of biocides (Orhan, 2020). This concern stems from research showing that exposure to triclosan can lead to bacterial target mutations that confer isoniazid resistance and designates for mutants with sensitivity to multiple antimicrobial medicines via the formation of multidrug-resistant efflux pumps, as described in Freundlich et al (2009).…”
Section: Antibiotic Susceptibility Testing and Mar Index Evaluationmentioning
confidence: 99%
“…TCS has shown diverse activities as an antimicrobial agent; indeed, several reports describe its antibacterial and antifungal activity, also against biofilms [ 63 , 64 ]. TCS has demonstrated high biocidal and durable activity on polyester and cotton surfaces for medical textile applications [ 65 ]. To a lesser extent, triclosan is used in textiles and plastics (sportswear, bed clothes, shoes, carpets) to control the growth of disease or odor-causing bacteria [ 66 ].…”
Section: Pharmacological Activities Of Tcsmentioning
confidence: 99%
“…This fiber strongly resists to the direct attack of microorganisms due to their molecular structure. However, it also induces higher perspiration, which commonly results in discomfort and microbial growth when it is used in direct contact with the skin [3]. In particular, textiles used in medical applications are in close contact to the human body for a long time, hence they are prone to increase the risk of infection [4].…”
Section: Introductionmentioning
confidence: 99%